2016
DOI: 10.1080/01596306.2016.1274290
|View full text |Cite
|
Sign up to set email alerts
|

Invited to labour or participate: intra- and inter-generational distinctions and the role of capital in children’s invited participation

Abstract: This paper applies aspects of Bourdieu's conceptual toolkit related to capital, and analyses inter-and intra-generational relations of influence. Applying Bourdieu's concepts to examples of case studies from a children's parliament in Finland, and with reference to an adult resident forum, moments of continuity and disruption in the relatively stable patterns of distinction between children and adults emerge. Children in school councils (at times) are labourers for agendas set by teachers, but the children at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Radical social work might therefore again be inspired by Freirean forms of participatory action (for example, Rogowski, 1995, Larkins, 2016 and, for example, the Black Lives Matter movement; these are 'making a difference' activities that focus on bringing about change through critical reflection and action, raising consciousness about barriers and continuing action to achieve change. It must involve linking children and young people's concerns to wider policy decisions and mechanisms in order to hold political decision-making to account (for example, Larkins, 2011;Kiili and Larkins, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radical social work might therefore again be inspired by Freirean forms of participatory action (for example, Rogowski, 1995, Larkins, 2016 and, for example, the Black Lives Matter movement; these are 'making a difference' activities that focus on bringing about change through critical reflection and action, raising consciousness about barriers and continuing action to achieve change. It must involve linking children and young people's concerns to wider policy decisions and mechanisms in order to hold political decision-making to account (for example, Larkins, 2011;Kiili and Larkins, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stronger action-orientation practice focused on social justice would provide greater potential to achieve the changes that children and young people seek, and to understand the conditions that are limiting these changes. At the same time, caution and critical awareness are also needed as reviews of co-production and child participation have shown that neo-liberal participatory practice can be a means of responsibilising service users of any age (Beresford, 2008;Needham and Carr, 2009;Kiili and Larkins, 2018) placing greater emphasis on individual's responsibility to care for themselves and denying them the social resources (or control over these) that would enable them to direct social action. Further, current financial "austerity" measures and shifting working environments in which child protection services shuffle between being outsourced and then brought back into local authorities are limiting opportunities for professionals to dedicate the time needed to develop continuity of relationships and to be able to share and learn from each other's examples of effective protective participatory practice.…”
Section: Discussionmentioning
confidence: 99%
“…As a social structural category, the generational order(s) is always present, if not necessarily that visibly or always the most important standpoint, but it is invariably there (Punch, 2020;Alanen and Mayall, 2001). The current literature on children's collective participation emphasises the importance of intergenerational relations and calls for a focus on the generational difference (Cuevas-Parra and Tisdall, 2019;Kiili and Larkins 2018;Moran-Ellis and Sü nker, 2018). Although our study is confined to professionals' views, it does enable us to unpick meanings given to children's service user involvement.…”
Section: Children Adults and Intergenerational Relationsmentioning
confidence: 99%